Retromuscular Mesh Repair Using Fibrin Glue: Early Outcomes and Cost-effectiveness of an Evolving Technique - Irfan A. Rhemtulla, MD, MS; Michael G. Tecce, DO; Robyn B. Broach, PhD; Charles A. Messa, IV, BS; Jaclyn T. Mauch, BA; John P. Fischer, MD, MPH (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Retromuscular hernia repairs (RHRs) decrease hernia recurrence and surgical site infections but can cause significant pain. We aimed to determine if pain and postoperative outcomes differed when comparing suture fixation (SF) of mesh to fibrin glue fixation (FGF). Methods:. Patients undergoing RHR (n = 87) between December 1, 2015 and December 31, 2017 were retrospectively identified. Patients received SF of mesh (n = 59, 67.8%) before the senior author changing his technique to FGF (n = 28, 32.2%). These 2 cohorts were matched (age, body mass index, number of prior repairs, mesh type, defect size, and wound class). Outcomes were analyzed using a matched pairs design with multivariable linear regression. Results:. Two matched groups (21 FGF and 21 SF) were analyzed (45.2% female, average age 56 years, average body mass index 34.7 kg/m2, and average defect size 330 cm2). Statistical significance was observed for FGF compared with SF: length of stay (3.7 versus 7.1 days, P = 0.032), time with a drain (17.2 versus 27.5 days, P = 0.012), 30-day postoperative visits (2 versus 3, P = 0.003), pain scores (5.2 versus 3.1, P = 0.019) and activity within the first 24 hours (walking versus sitting, P = 0.002). Operative time decreased by 23.1 minutes (P = 0.352) and postoperative narcotic represcription (3 versus. 8 patients, p=0.147) also decreased. Average cost for patients receiving SF was $36,152 compared to $21,782 for FGF (P = 0.035). Conclusions:. Sutureless RHR using FGF may result in decreased pain when compared with a matched cohort receiving SF, translating to enhanced recovery time, shortened hospital stay, and decreased costs.